Removal of Phenol in Aqueous Solution by Nanocrystalline TiO2/Activated Carbon Composite Catalyst - Chalermpan Ngamsopasiriskun,; Saijai Charnsethikul,; Surachai Thachepan,; Apisit Songsasen, (Agriculture and Natural Resources, 2010)
A nanocrystalline TiO2/activated carbon composite catalyst (TiO2/AC) was prepared by the sol-gel method in isopropanol mixed with activated carbon (AC). The preparation of TiO2/AC was calcined at 400°C and characterized. The X-ray diffraction (XRD) pattern indicated that the TiO2/AC was in the anatase phase. The transmission electron microscopy (TEM) image showed that the crystallite size of TiO2/AC was in the range of 7-9 nm. The specific surface area from the Brunauer, Emmett and Teller (BET) method was 441m2/g and the adsorption capacity determined from the adsorption isotherm was 5.0×104 mg/g. The TiO2/AC calcined at 400°C was used to remove phenol in aqueous solution under UV irradiation, which showed the highest removal efficiency when compared with TiO2 (Degussa- P25) and AC. The percentage removal of 100 ppm phenol by 0.4 g of TiO2/AC in 4 h was 68.03%, due to both adsorption (54.14%) and photocatalytic degradation (13.88%), with the highest rate constant being 0.1080 h-1.